Spatiotemporal distribution of paralytic shellfish poisoning (PSP) toxins in shellfish from Argentine Patagonian coast - Gracia Villalobos, Leilén (Heliyon, 2019)
Harmful algal blooms (HABs) have been recorded in the Chubut Province, Argentina, since 1980, mainly associated with the occurrence of paralytic shellfish poisoning (PSP) toxins produced by dinoflagellates of the genus Alexandrium. PSP events in this area impact on fisheries management and are also responsible for severe human intoxications by contaminated shellfish. Within the framework of a HAB monitoring program carried out at several coastal sites along the Chubut Province, we analyzed spatiotemporal patterns of PSP toxicity in shellfish during 2000–2011. The highest frequency of mouse bioassays exceeding the regulatory limit for human consumption was detected in spring and summer, with average values of up to ≈70% and 50%, respectively. By contrast, a lower percentage of positive bioassays (2–8%) or no toxicity at all was usually detected during autumn and winter. The most intense PSP events were usually observed between November and January, with values of up to 4,000 μg STX eq 100 g(−1), and showed a marked interannual variability both in their magnitude and location. In addition, a severe PSP outbreak was recorded during autumn, 2009, at Camarones Bay, with toxicity values of up to 14,000 μg STX eq 100 g(−1). The scallop Aequipecten tehuelchus showed significantly higher toxicity values compared to other shellfish species in SJG and SMG, suggesting a lower detoxification capacity. Our results contribute to the understanding of HABs dynamics on the Argentine Patagonian coast.